Synthesis of Cellulose Acetate From Coil Waste (Borassus flabellifer L) Using Delignification Time Variations: Sintesis Selulosa Asetat Dari Limbah Sabut Lontar (Borassus flabellifer L) dengan Menggunakan Variasi Waktu Delignifikasi - Batu, Matius Stefanus; Kolo, Maria Magdalena; Rika, Fransiska (Stannum : Jurnal Sains dan Terapan Kimia, 2024)
Synthesis of cellulose acetate form palm coir (Borassus flabellifer L) waste has been synthesized by varying the time in the delignification process. This study aimed to determine the characteristics of cellulose acetate form palm coir waste (Borassus flabellifer L) and the optimum time for the delignification process. This research was conducted in several stages: sample preparation, cellulose isolation (delignification and bleaching process), and synthesis of cellulose acetate (activation, acetylation, and hydrolysis process). The cellulose acetate obtained was then charatecrized by testing for water content, acetyl content, and degree of substitution and functional grup analysis using a fourier transform infra-red (FTIR) spectrophotometer. In the delignification process, variations of the delignification time were usesd, namely 60, 90, 120, and 150 minutes. Form the results of the study, the characteristics of cellulose acetate in palm coir were optained, namely water content of 0.95%‒2.16%, acetyl content of 37.19%‒40.85%, degree of substitution of 2.2‒2.6 and identification of functional groups using FTIR showed that there was a typical absorption of cellulose acetate on the carbonyl group (C=O) and the ester group (C-O acetyl). The results of variations in the time of the delignification process showed that the optimum reaction time was 120 minutes with the yield of cellulose acetate produced at 254.4%, water content 2.16%, acetyl content 40.85%, degree of substitution (DS) 2.6. the cellulose acetate produced belongs to the type of cellulose diacetate, which can be further utilized in manufacturing threads, membranes, adhesives of films, and mask filters.